Somatic embryogenesis, organogenesis and callus growth kinetics of flax (Linum usitatissimum L.) - Cunha, Ana (1996)
The effects of plant growth regulators (PGR) on calli induction, morphogenesis and somatic embryogenesis of flax were studied. The organogenic and callus formation capacity were assessed for different types of source explants. Root and shoot explants were equally good material for calli production but the former produced calli without shoot regeneration capacity. Under the experimental conditions tested, 2,4-dichlorophenoxyacetic acid (2,4-D) + zeatin (ZEA) was the most efficient PGR combination on calli induction and biomass production. The calli were green but with no rhizogenic capacity. On the contrary, and at similar concentrations, indole-3-butyric acid (IBA) + kinetin (KIN) induced white or pale green friable calli with a good root regeneration capacity (60%). A factorial experiment with different combinations of 2,4-D + ZEA + gibberellic acid (GA3) levels revealed that the direction of explant differentiation was determined by specific PGR interactions and concentrations. The results from these experiments revealed that the morphogenetic pathway (shoot versus root differentiation) can be manipulated on flax explants by raising the 2,4-D level from 0.05 to 3.2 mg l-1 in the induction medium. The induction and development of somatic embryos from flax explants was possible in a range of 2,4-D+ZEA concentrations surrounding 0.4 mg l-1 2,4-D and 1.6 mg l-1 ZEA, the most efficient phytohormonal combination.